ANALISIS FINANSIAL DAN STRATEGI PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH AMPLANG MENUJUONE VILLAGE ONE PRODUCT - Cholid, Irfan (Universitas Djuanda, 2020)
The Micro, Small and Medium Enterprises (MSME) sector in Indonesia has some important roles in development, one of which is MSMEs are able to reduce unemployment due to labor force that is not absorbed in the world of work. One of the village development efforts is through One Village One Product approach. Kauman Village is the center of amplang MSME which is considered by the community to be a typical product of the area and has been operating for years and still exists up to today. Despite being operated for a while, its financial feasibility has not been recognized. In addition, business development strategies are also essential because until now most of these MSMEs still face challenges which one of them is on the marketing aspect. The marketing strategy used is conventional one, which is considered less suitable for today’s digital era. The analytical method used to determine the financial condition ofamplang’s business in KaumanVillage,Ketapang is by calculating the net profit of the business. While the SWOT analysis is used to formulate the amplang MSME development strategy in Kauman Village based on the respondents’ answers on the questionnaires. Based on the results of the financial analysis with net profit calculation, it can be concluded that all amplang MSMEs are feasible to maintain. Meanwhile, according to the results of the SWOT analysis, all amplang MSMEs are positive and in quadrant I which proves that amplangMSMEs are very strong and have a chance to grow and develop.